The ambassadors of Charles I of Hungary in the papal curia (1301-1342) - Maleth, Agnes (Publications de l’École française de Rome, 2019)
The examination of the personnel of the diplomatic relations between the Kingdom of Hungary and the papacy in the XIVth century implies on one hand the analysis of the work of papal legates and collectors in Hungary, and the research of the delegations of the ambassadors of the Hungarian king in the papal curia on the other hand. The corpus of the sources in the first case is quite advantageous. Not only the documents of the legation of Gentilis de Monteflorum (the cardinal sent by Clement V to...